2010
DOI: 10.1111/j.1469-8137.2010.03459.x
|View full text |Cite
|
Sign up to set email alerts
|

OsHMA3, a P1B‐type of ATPase affects root‐to‐shoot cadmium translocation in rice by mediating efflux into vacuoles

Abstract: Summary• The cadmium (Cd) over-accumulating rice (Oryza sativa) cv Cho-Ko-Koku was previously shown to have an enhanced rate of root-to-shoot Cd translocation. This trait is controlled by a single recessive allele located at qCdT7.• In this study, using positional cloning and transgenic strategies, heavy metal ATPase 3 (OsHMA3) was identified as the gene that controls root-to-shoot Cd translocation rates. The subcellular localization and Cd-transporting activity of the gene products were also investigated.• Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
357
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(388 citation statements)
references
References 35 publications
10
357
2
1
Order By: Relevance
“…QTL analyses, including ours, identified major QTLs responsible for the high-Cd trait of these three cultivars in almost identical regions on chromosome 7 (Tezuka et al 2010, Ueno et al 2009). Very recently, it has been revealed that OsHMA3, a P 1B -type ATPase, is encoded by a gene within the QTL region on chromosome 7 and plays an important role in controlling shoot Cd accumulation in rice (Miyadate et al 2011, Ueno et al 2010. Functional assays by heterologous expression of OsHMA3 in yeast showed that low-Cd cultivars contain a functional version of this gene, which is involved in Cd storage in root vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…QTL analyses, including ours, identified major QTLs responsible for the high-Cd trait of these three cultivars in almost identical regions on chromosome 7 (Tezuka et al 2010, Ueno et al 2009). Very recently, it has been revealed that OsHMA3, a P 1B -type ATPase, is encoded by a gene within the QTL region on chromosome 7 and plays an important role in controlling shoot Cd accumulation in rice (Miyadate et al 2011, Ueno et al 2010. Functional assays by heterologous expression of OsHMA3 in yeast showed that low-Cd cultivars contain a functional version of this gene, which is involved in Cd storage in root vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…Good evidence was presented for the involvement of Ni-histidine complexes in the vacuolar compartmentation of Ni and as a consequence in the retention of this heavy metal in roots [59]. A heavy metal ATPase was suggested to be involved in Cd accumulation in vacuoles of root cells causing Cd retention in roots and decreasing the transport to the shoot [66].…”
Section: Transport With the Transpiration Stream In The Xylemmentioning
confidence: 99%
“…After the release into the root xylem, free or chelated ions flow with the xylem sap upwards (Figure 2). Important for the concentration of heavy metals in the transpiration stream are xylem loading in the roots, interactions with cell walls during acropetal transport and selective removal from the xylem sap [65,66,68,69]. If there would be no further redistribution, the heavy metals would accumulate primarily in photosynthetically active (transpiring) leaves.…”
Section: Transport With the Transpiration Stream In The Xylemmentioning
confidence: 99%
“…Among rice P-type ATPases characterized, OsHMA2 transports Zn and Cd (Satoh-Nagasawa et al, 2012;Takahashi et al, 2012;Yamaji et al, 2013), OsHMA3 is involved in Cd accumulation (Ueno et al, 2010;Miyadate et al, 2011), and OsHMA9 is responsible for the transport of Zn, Cu, Pb, and Cd (Lee et al, 2007). Knockout of OsHMA5 only resulted in altered Cu concentration, but not other metals, including Zn, Fe, and Mn (Fig.…”
Section: Transport Activity Of Oshma5 In Yeastmentioning
confidence: 99%
“…Furthermore, OsHMA2 at the node is required for preferential distribution of Zn to young leaves and panicles (Yamaji et al, 2013). OsHMA3 is localized to the tonoplast of the root cells and responsible for the sequestration of Cd into the vacuoles (Ueno et al, 2010;Miyadate et al, 2011). On the other hand, OsHMA9 was mainly expressed in vascular tissues, including the xylem and phloem (Lee et al, 2007).…”
mentioning
confidence: 99%